The novel atypical retinoid ST5589 down‐regulates Aurora Kinase A and has anti‐tumour activity in lymphoma pre‐clinical models. (3rd August 2015) - Bernasconi, Elena; Gaudio, Eugenio; Kwee, Ivo; Rinaldi, Andrea; Cascione, Luciano; Tarantelli, Chiara; Mensah, Afua Adjeiwaa; Stathis, Anastasios; Zucca, Emanuele; Vesci, Loredana; Giannini, Giuseppe; Bertoni, Francesco
Summary Despite the marked improvements in the treatment of lymphomas, there is still a need for new therapeutic agents. Synthetic retinoids represent a class of compounds with anti‐cancer activity. Here, we report the preclinical activity of a new member of this class, the ST1926‐derivative ST5589, in lymphomas. ST5589 presented a dose‐dependent anti‐proliferative activity in almost all of the 25 lymphoma cell lines analysed, with a median 50% inhibitory concentration of 433 nM. Apoptosis was observed in 8/11 cell lines. ST5589 induced changes in the gene expression profiles of the cell lines, including the down‐regulation of Aurora Kinase A (AURKA). Specific gene expression signatures were associated with a higher sensitivity to the compound and combination of ST5589 with carfilzomib revealed the importance of proteasome activity in mediating the anti‐tumour activity of ST5589. In conclusion, we have identified a new mechanism of action of atypical retinoids as anti‐cancer compounds, and the encouraging results obtained with the new ST1926‐derivative ST5589 provide the basis for further developments of the compound.